The Relationship Between Job Satisfaction and Turnover Intention for Nursing HR at Hermina Bogor Hospital - Larasati, Sindhy; Rahmawati, Siti (Jurnal Ilmiah Sumber Daya Manusia, 2023)
Nonideal turnover is a frequent problem that occurs in hospital management. The biggest contributor factor to turnover is dissatisfaction with human resources in hospitals. People who feel dissatisfied with their job will leave their job. Therefore, this study aims to analyze nursing human resources' perceptions of job satisfaction and turnover intention and the relationship between job satisfaction and turnover intention of nursing human resources in ICU and in-patient rooms at Hermina Bogor Hospital by using descriptive analysis and Pearson correlation. This study used saturated sampling with 69 respondents. Based on the descriptive analysis, the perceptions of human resources for nursing both in the ICU and inpatient rooms regarding job satisfaction are satisfied and high turnover intention. Based on Pearson correlation analysis.